An overview of the occurrence of ether- and ester-linked iso-diabolic acid membrane lipids in microbial cultures of the Acidobacteria: Implications for brGDGT paleoproxies for temperature and pH. (October 2018) - Sinninghe Damsté, Jaap S.; Rijpstra, W. Irene C.; Foesel, Bärbel U.; Huber, Katharina J.; Overmann, Jörg; Nakagawa, Satoshi; Kim, Joong Jae; Dunfield, Peter F.; Dedysh, Svetlana N.; Villanueva, Laura
Highlights: Only 2 out of 46 acidobacterial strains representing 7 subdivisions contain brGDGTs. Strains of SDs 1, 3, 4, and 6 produce their building block, i.e. iso -diabolic acid. Iso -diabolic acid occurs in a (mono) ether-bound form in SD 4 Acidobacteria. The gene cluster responsible for the formation of this ether bond is identified. Methylation of iso -diabolic acid occurs at C-5 and C-6 as observed for brGDGTs. Abstract: 13, 16-Dimethyl octacosanedioic acid ( iso -diabolic acid) is a major membrane-spanning lipid of subdivisions (SDs) 1, 3 and 4 of the Acidobacteria, a highly diverse phylum within the Bacteria. It has been suggested that these lipids are potential building blocks for the orphan bacterial glycerol dialkyl glycerol tetraethers (GDGT) that occur widely in a variety of environmental settings. Here, we expand the knowledge on the occurrence of iso -diabolic acid in Acidobacteria by examining the lipid composition of six strains belonging to SDs 6, 8, 10, and 23 of the Acidobacteria, not previously analyzed for these lipids. In addition, we examined 12 new strains belonging to SDs 1, 3 and 4. Acid hydrolysis of total cell material released iso -diabolic acid in substantial quantities (25–39% of all fatty acids) from the strains of SDs 1 and 3 (except " Candidatus Solibacter usitatus"), and, for the first time, strains of SD 6 (6–25%), but not from SDs 8, 10, and 23. The monoglycerol ether derivative of iso -diabolic acid was only dominantly present in SD 4 strains (17–34%), indicating that the occurrence of ether-bound iso -diabolic acid is mainly restricted to SD 4 species. Methylated iso -diabolic acid derivatives were encountered in SDs 1, 3, 4, and 6, but only SD 4 species produced 5-methyl iso -diabolic acid derivatives, whereas the other SDs formed 6-methyl iso -diabolic acids. This suggests that the position of methylation of iso -diabolic acid may be controlled by the phylogenetic affiliation within the Acidobacteria and thus may not be a direct but an indirect response environmental to environmental conditions as inferred from the bacterial GDGT distributions in soil, peat and rivers.